The first report of the human platelet alloantigen 4b allele in a Brazilian - Toralles-Pereira, C.; Pardini, MIDC; Deffune, Elenice [UNESP]; Machado, PEA (Blackwell Publishing, 2005)
The human platelet alloantigen (HPA) 4b allele is rarely observed in Caucasians and the observed incidence in Asians is usually lower than 1.0%. We report the first Brazilian with the allele HPA-4b, and were able to determined that he inherited it from his father.